Allowing the Data to Speak Freely: The Macroeconometrics of the Cointegrated Vector Autoregression - Hoover, Kevin D; Johansen, Søren; Juselius, Katarina (American Economic Review, 2008)
Allowing the Data to Speak Freely: The Macroeconometrics of the Cointegrated Vector Autoregression by Kevin D. Hoover, Soren Johansen and Katarina Juselius. Published in volume 98, issue 2, pages 251-55 of American Economic Review, May 2008